1995
DOI: 10.1073/pnas.92.11.4987
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a MAGE gene family in the Xp21.3 region.

Abstract: A human gene with strong homology to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…Similarly, an FXXLF motif-dependent interaction was observed in the presence of DHT between GST-AR4-52 and 35 S-labeled AR624-919 containing the AR ligand binding domain. 35 S-labeled MAGE-11 migrates a 70 kDa, and 35 S-labeled AR ligand binding domain migrates a 41 kDa. We tested a previously described AR nuclear transport mutant, ARm4, that contains mutations in the AR bipartite nu- Immunoblots of GAL-AR peptides were performed using extracts from COS cells (2 ϫ 10 6 /10-cm dish) transfected with 10 g of GAL-AR peptide DNA with DEAEdextran.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an FXXLF motif-dependent interaction was observed in the presence of DHT between GST-AR4-52 and 35 S-labeled AR624-919 containing the AR ligand binding domain. 35 S-labeled MAGE-11 migrates a 70 kDa, and 35 S-labeled AR ligand binding domain migrates a 41 kDa. We tested a previously described AR nuclear transport mutant, ARm4, that contains mutations in the AR bipartite nu- Immunoblots of GAL-AR peptides were performed using extracts from COS cells (2 ϫ 10 6 /10-cm dish) transfected with 10 g of GAL-AR peptide DNA with DEAEdextran.…”
Section: Resultsmentioning
confidence: 99%
“…However, a related MAGEB family of genes was recently reported that is ϳ60% homologous to the MAGE (MA-GEA) family (32). The MAGEB gene family maps to the Xp21 region of the X chromosome and is associated with a dosesensitive sex reversal phenotype (29,32,35) and with the DAX-1 gene, where mutations cause X-linked adrenal hypoplasia congenita and hypogonadotropic hypogonadism (34).…”
Section: Vol 25 2005 Mage-11 Binds the Ar Fxxlf Motif 1249mentioning
confidence: 99%
“…Since 1991, MAGE-1 (melanoma associated antigen) gene has been cloned from melanoma cells (van der Bruggen et al, 1991), there are up-to-date 17 MAGE genes being cloned (De Plaen et al, 1994;Lucas et al, 1998;Lurquin et al, 1997;Muscatelli et al, 1995;van der Bruggen et al, 1991). The MAGE genes are activated in spermatozoa but silent in normal somatic cells.…”
mentioning
confidence: 99%
“…This is due to the characterization of malignant tumors by melanoma, and due to the fact that low levels that are typically found in normal tissues, with the exception of the testicles and placenta (20). However, Jang et al discovered that MAGE mRNA was detected in corresponding normal tissues (21), and in 2006 Ito et al also revealed that MAGED4 expression was detected at low levels in normal tissues (19).…”
Section: Discussionmentioning
confidence: 99%